2002
DOI: 10.1042/cs20010236
|View full text |Cite
|
Sign up to set email alerts
|

Molecular forms of adrenomedullin in pericardial fluid and plasma in patients with ischaemic heart disease

Abstract: Experimental studies have demonstrated that adrenomedullin (AM) has a positive inotropic action and exerts inhibitory effects against ventricular remodelling as an autocrine and paracrine factor. However, there is no clinical evidence for AM acting as a local regulator in the human heart. We measured the levels of various molecular forms of AM, i.e. an active form of mature AM (AM-m), an intermediate inactive form of glycine-extended AM (AM-Gly) and total AM (AM-T=AM-m+AM-Gly), in plasma and pericardial fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Pericardial fluid contains abundant various bioactive substances produced in the heart10 11 and its composition is similar to the interstitial fluid in the ventricle 19. In addition, the concentrations of bioactive substances, such as adrenomedullin, BNP, ANP, basic fibroblast growth factor and vascular endothelial growth factor, are higher in pericardial fluid than in plasma 12 13 19 20. Our study demonstrated that most IR-BNP is present as IR-proBNP-108, irrespective of the type of heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pericardial fluid contains abundant various bioactive substances produced in the heart10 11 and its composition is similar to the interstitial fluid in the ventricle 19. In addition, the concentrations of bioactive substances, such as adrenomedullin, BNP, ANP, basic fibroblast growth factor and vascular endothelial growth factor, are higher in pericardial fluid than in plasma 12 13 19 20. Our study demonstrated that most IR-BNP is present as IR-proBNP-108, irrespective of the type of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after the incision of the pericardium, undiluted pericardial fluid was obtained as reported previously 12 13. At the same time, blood was withdrawn from the cannulated brachial artery.…”
Section: Methodsmentioning
confidence: 99%
“…It has been postulated that ADM acts as a cardiac autocrine and paracrine factor. Cardiac secretion of ADM is associated with left ventricular dysfunction, ventricular overload and myocardial ischemia (Nishikimi et al. , 2002, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Detection of ADM blood plasma levels. ADM occurs in two molecular forms, the active and mature ADM (m-ADM) form and the inactive and glycine-extended ADM (gly-ADM) form (22). Total ADM (t-ADM) is the sum of the levels of m-ADM and gly-ADM.…”
Section: Methodsmentioning
confidence: 99%